From cross-border cooperation to European integration and global economic movements - Кифяк, Олександр; Kyfiak, Vasyl (Kyiv : KNUTE, 2019)
The article focuses on changes in the legislation of Ukraine concerning crossborder cooperation and its organizational foundations. According to the survey of scientists, practitioners, representatives of local authorities and public organizations, the definition of «unification of European and regional cooperation with the status of a legal entity» as a socially recognized organizational and legal form of collective socio-economic activity is proposed. Based on the analysis of socio-economic development of a number of regions of Ukraine in 2017, which are territorially located from the Center to the West, it is confirmed that the development of regions in Ukraine occurs from the center to the periphery and the reasons of this situation have been identified. The ways and additional opportunities for the development of crossborder cooperation and its impact on European integration processes and global economic shifts are highlighted. The role of cross-border cooperation in increasing exports and imports of goods and services has been identified on the example of international trade in cross-border regions with the EU countries.
Keywords: cross-border cooperation, European integration, social and economic development